Superficial branch of the radial nerve passing through the supinator canal, emerging between the extensor digitorum and abductor pollicis longus muscles and consequently supplying the second finger and radial portion of the third finger: a case report and clinical implications - Khadanovich, Anhelina; Benes, Michal; Kaiser, Radek; Kachlik, David (Surgical and radiologic anatomy, 2024)
Awareness of unique path of the superficial branch of the radial nerve and its unusual sensory distribution can help avoid potential diagnostic confusion. We present a unique case encountered during a routine dissection of a Central European male cadaver. An unusual course of the superficial branch of the radial nerve was found in the right forearm, where the superficial branch of the radial nerve originated from the radial nerve distally, within the supinator canal, emerged between the extensor digitorum and abductor pollicis longus muscles and supplied the second and a radial half of the third digit, featuring communications with the lateral antebrachial cutaneous nerve and the dorsal branch of the ulnar nerve. Due to dorsal emerging of the superficial branch of the radial nerve the dorsal aspect of the thumb was innervated by the lateral antebrachial cutaneous nerve. To our best knowledge such variation of the superficial branch of the radial nerve has never been reported before. This variation dramatically changes aetiology and manifestation of possible entrapment syndromes which clinicians should be aware of.
Keywords: nervus radialis; Cadaver; anatomická variace; Lateral antebrachial cutaneous nerve; Forearm; Humans; Variation; Dissection; Fingers; lidé; Sensory distribution; Superficial branch of radial nerve; kosterní svaly; Communication; předloktí; prsty ruky; Male; disekce; Muscle, Skeletal; Radial Nerve; Supinator canal; mrtvola; mužské pohlaví; Anatomic Variation